Fruit bagging improves colour and quality in apple - Sharma, R R; Asrey, Ram; Pal, R K (Indian Horticulture, 2019)
Introduction: Colour development is a problem in apple fruits at lower hills. For the development of good colour in apple fruits, enthral is usually sprayed on trees, which may pose threat to tree health and the Himalayan ecosystem. Further, apple suffers from several diseases and disorders, for which many pesticides are sprayed, the residues of which are injurious to human beings. Hence, an eco- and farmer-friendly alternative technology of fruit-bagging has been developed for apple. Its use is helpful for better colour development, quality enhancement and reduction in insects, diseases and disorders. Finally, dependency on chemicals is reduced with augmented farming income.